West Syndrome: How Early is Early for its Presentation? - Shrestha, Bikash; Kiran, Kamal; Ghulliani, Ranjit (Journal of Nepal Paediatric Society, 2013)
West syndrome is the triad of mental retardation, infantile spasms and characteristic hypsarrhythmia on electroencephalograph. West syndrome usually presents in mid-infancy period. We present this as a rare presentation of West syndrome in the neonatal period. DOI: http://dx.doi.org/10.3126/jnps.v33i3.8639 J. Nepal Paediatr. Soc. 2013;33(3):239-242